2012
DOI: 10.1212/wnl.78.1_meetingabstracts.p05.101
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D3 Concentration Correlates with the Severity of Multiple Sclerosis (P05.101)

Abstract: Background:To investigate the possible association between serum 25(OH) vitamin D3 concentration and the severity of disease in Iranian patients with multiple sclerosis (MS) and to compare this concentration with a matched control group.Methods:This was an analytical cross-sectional study performed at Jondishapour Neurology Clinic in Tehran, Iran. Patients with relapsing–remitting MS were categorized by disease severity: mild [0≤ Expanded Disability Status Scale (EDSS) ≤3], moderate (3.5≤EDSS≤5.5), and severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
2
13
0
4
Order By: Relevance
“…Interestingly, migration studies have shown that MS risk changes with migration from one place to another; however, age at migration plays a key role in determining the disease risk of the migrant (58,59). Recent studies have suggested an association between vitamin D levels and MS relapse rate as well as the degree of disability, and it was seen that patients with higher serum levels of vitamin D showed a lower relapse rate while lower levels of vitamin D appeared to be associated with higher levels of disability in patients measured in terms of expanded disability status scale (EDSS) score (60)(61)(62)(63).…”
Section: Ms Risk and Vitamin Dmentioning
confidence: 99%
“…Interestingly, migration studies have shown that MS risk changes with migration from one place to another; however, age at migration plays a key role in determining the disease risk of the migrant (58,59). Recent studies have suggested an association between vitamin D levels and MS relapse rate as well as the degree of disability, and it was seen that patients with higher serum levels of vitamin D showed a lower relapse rate while lower levels of vitamin D appeared to be associated with higher levels of disability in patients measured in terms of expanded disability status scale (EDSS) score (60)(61)(62)(63).…”
Section: Ms Risk and Vitamin Dmentioning
confidence: 99%
“…Given the recent changes in MS incidence in Iran, it is possible that studying environmental risk factors in this population may provide a better understanding of true risk factors for MS. Studies of 25-hydroxyvitamin D levels in Iranian MS patients have been conflicting, with some studies showing no difference between patients and controls (Eskandari et al, 2015;Nikanfar et al, 2015), one study showing an effect on risk but no relation with disability (Nikanfar et al, 2015), and finally other studies showing an association with risk and/or disability (Shahbeigi et al, 2013;Harandi et al, 2012;Mazdeh et al, 2013). One of the reasons for the discrepancies between studies may be the use of relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Pilot studije su takođe pokazale pozitivne efekte suplementacije vitamina D na nivoe citokina, njihovu bezbednost i podnošenje kod pacijenata sa multiplom sklerozom. Ova istraživanja su takođe postavila pitanje da li su niski nivoi serumskog vitamina D predisponirajući za nastanak multiple skleroze ili njena posledica zbog nedovoljne izloženosti uV zračenju sunca usled nastale invalidnosti (35).…”
Section: Multipla Skleroza I Vitamin Dunclassified